Impact assessment of social assistance for education on welfare distribution: A microsimulation approach using INDOMOD - Achmad Budi Setyawan; Rina Karlina; Retno Maruti; Galuh Chandra Wibowo; Yiska Dini Nastiti (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2025)
Social assistance for education is one of several instruments in Indonesia to support poor and vulnerable people. There are two main programs which is Family Hope Program (PKH) and Smart Indonesia Program (PIP). Analyzing the distributional impact to both programs is very important to improve program's effectiveness and efficiency. INDOMOD, a tax-benefit microsimulation model for Indonesia, was used in this study to evaluate the distributional effect of these programs to poverty and inequality, using Susenas as the main data. Several results from this study showed that the revocation of the education component of PKH has a more significant impact on poor and vulnerable groups than the revocation of PIP. Further, the revocation of the education component of PKH has a more significant effect on households with children than the revocation of PKH.
Keywords: 330; social assistance; education; microsimulation; indomod